1997
DOI: 10.1046/j.1423-0410.1997.7220079.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Anti‐HBc Reactivity Reflect ‘Lifestyle’ Risk in North London Blood Donors?

Abstract: Blood from donors positive for both anti-HBc and anti-HBs should be considered suitable for transfusion purposes. This is consistent with the practice of accepting blood from naturally immune donors for preparation of hepatitis B immunoglobulin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…We found anti-HBc to be associated with known risk factors for hepatitis B, and thus a surrogate marker for risk behaviour, but the literature is conflicting on this issue: Moore et al . found no difference in risk behaviour, but the anti-HBc-negative group was small [6]. Molijn et al .…”
Section: Discussionmentioning
confidence: 94%
“…We found anti-HBc to be associated with known risk factors for hepatitis B, and thus a surrogate marker for risk behaviour, but the literature is conflicting on this issue: Moore et al . found no difference in risk behaviour, but the anti-HBc-negative group was small [6]. Molijn et al .…”
Section: Discussionmentioning
confidence: 94%
“…Continuation of anti‐HBc screening has been questioned, however 17 . In a study from North London, 18 anti‐HBc reactivity was not found to reflect a “lifestyle” risk when anti‐HCV– and HBsAg‐positive donors were excluded although the authors state that this may not be the case in other populations of the United Kingdom with a different seroprevalence of hepatitis B markers. It may not necessarily be true for Sweden either, where there is a very low prevalence of hepatitis B.…”
Section: Discussionmentioning
confidence: 99%
“…10 case-control studies tried to identify risk factors for TTI in blood donors. The cases included blood donors with a viral infection with HIV-1 [ 13 ], HBV [ 14 , 16 ], or HCV [ 11 , 15 , 17 , 18 , 21 , 23 , 24 ], and the controls were donors who did not have this particular infection. Studies only looking at blood donors with infections were not included.…”
Section: Resultsmentioning
confidence: 99%
“…For the risk of HBV infection, we found limited evidence from 2 observational studies from 1997 and 2001, but a statistically significant correlation could not be demonstrated between MSM and HBV infection in blood donors. The reason for this is a low number of events and a large variability of the results, reflected in wide confidence intervals [ 14 , 16 ].…”
Section: Resultsmentioning
confidence: 99%